Identification of App1 as a regulator of phagocytosis and virulence of Cryptococcus neoformans - Luberto, Chiara (American Society for Clinical Investigation, 2003)
Cryptococcus neoformans is a fungal pathogen that, after inhalation, can disseminate to the brain. Host alveolar macrophages (AMs) represent the first defense against the fungus. Once phagocytosed by AMs, fungal cells are killed by a concerted mechanism, involving the host-cellular response. If the cellular response is impaired, phagocytosis of the fungus may be detrimental for the host, since C. neoformans can grow within macrophages. Here, we identified a novel cryptococcal gene encoding antiphagocytic protein 1 (App1). App1 is a cryptococcal cytoplasmic protein that is secreted extracellularly and found in the serum of infected patients. App1 does not affect melanin production, capsule formation, or growth of C. neoformans. Treatment with recombinant App1 inhibited phagocytosis of fungal cells through a complement-mediated mechanism, and Δapp1 mutant is readily phagocytosed by AMs. Interestingly, the Δapp1 mutant strain showed a decreased virulence in mice deficient for complement C5 (A/Jcr), but it was hypervirulent in mice deficient for T and NK cells (Tgε26). This study identifies App1 as a novel regulator of virulence for C. neoformans, and it highlights that internalization of fungal cells by AMs increases the dissemination of C. neoformans when the host cellular response is impaired.